FARMERS' ATTITUDES TOWARDS RICE FARMING INSURANCE IN MANARAP BARU VILLAGE, KERTAK HANYAR SUB-DISTRICT, BANJAR DISTRICT - Bayu Pratama Leksono; Ana Zuraida; Gusti Khairun Ni’mah (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
This study aimed to investigate the attitudes of farmers toward agricultural insurance programs and to explain the reasons for their participation or non-participation in these programs. Both primary and secondary data were used as sources of information. A total of 40 farmers were selected using stratified random sampling. The results revealed that program participants had a neutral attitude towards the Manarap Baru Village Rice Farmer Insurance Program (AUTP), with an index of 3.18. At the same time, non-participants tended to disagree, with an index of 2.54. The main reasons for farmers not participating in the AUTP program varied, with some citing a lack of understanding about the program despite efforts by the insurance company to provide direct counseling. Conversely, the reasons for farmers joining AUTP included various advantages, such as financial protection against the risk of crop failure, reduced loss risk, and an easy claims process in case of loss.